2006
DOI: 10.1371/journal.pgen.0020048
|View full text |Cite
|
Sign up to set email alerts
|

On the Mechanism of Gene Amplification Induced under Stress in Escherichia coli

Abstract: Gene amplification is a collection of processes whereby a DNA segment is reiterated to multiple copies per genome. It is important in carcinogenesis and resistance to chemotherapeutic agents, and can underlie adaptive evolution via increased expression of an amplified gene, evolution of new gene functions, and genome evolution. Though first described in the model organism Escherichia coli in the early 1960s, only scant information on the mechanism(s) of amplification in this system has been obtained, and many … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
235
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(244 citation statements)
references
References 76 publications
(133 reference statements)
8
235
1
Order By: Relevance
“…The two colony types described here have been reported previously in both E. coli (19) and S. enterica (9,20). Amplifications of the SJ type have been described in E. coli (21). In S. enterica, the two colony types show a less extreme ratio of stable to unstable Lac ϩ cell types, making it easier to identify the minority cell type.…”
supporting
confidence: 58%
See 1 more Smart Citation
“…The two colony types described here have been reported previously in both E. coli (19) and S. enterica (9,20). Amplifications of the SJ type have been described in E. coli (21). In S. enterica, the two colony types show a less extreme ratio of stable to unstable Lac ϩ cell types, making it easier to identify the minority cell type.…”
supporting
confidence: 58%
“…The identical nonindependent SJ junctions found in revertants from the first culture could not be detected by PCR in that culture, consistent with their rarity. Identical nonindependent SJ junctions were also observed in E. coli (21).…”
Section: No Stress-induced Event Is Required To Explain Formation Of Sjmentioning
confidence: 60%
“…Koszul et al (45) and Koszul and coworkers (46) identified an MH-mediated POL32-dependent replicative mechanism underlying segmental TD formation in S. cerevisiae. A genetic analysis of MH-mediated TD formation in Escherichia coli by Slack et al (47) implicated stalled replication as a trigger to the formation of these TDs. These observations are today collectively termed MMBIR (13,14).…”
Section: Tdp Is Characterized By the Coordinated Perturbation Of Severalmentioning
confidence: 99%
“…Gene duplicates can be found either as dispersed copies or in tandem arrays. While dispersed copies of gene duplicates arise commonly from segmental or whole genome duplication events or retroposition, tandem duplicates can be initiated from single-copy genes by repair of double-stranded DNA breakage and multiplied by unequal crossover events (Sturtevant 1925;Jelesko et al 1999;Blanc et al 2003;Soltis and Soltis 2003;Narayanan et al 2006;Slack et al 2006;Yandeau-Nelson et al 2006;Kong et al 2007;Freeling et al 2008).…”
mentioning
confidence: 99%